1997
DOI: 10.1002/(sici)1096-9861(19970120)377:3<381::aid-cne6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic input to nociceptive modulatory neurons in the rat rostral ventromedial medulla

Abstract: Within the rostral ventromedial medulla (RVM), there are two classes of putative pain modulation neurons: ON cells and OFF cells, which respectively burst or pause prior to withdrawal reflexes elicited by noxious stimulation. Alpha-adrenergic agonists injected into the RVM produce changes in the latency of spinal nocifensive reflexes and, when iontophoretically applied, alter the firing of RVM ON but not OFF cells. To provide further information about the contribution of norepinephrine to RVM neuron function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Our previous studies have shown that excitation of RVM Offcells, or primary cells identified in vitro, mediates the analgesia induced by PAG DAMGO, consistent with their proposed inhibitory action on spinal pain transmission (Pan et al, 1997;Fields and Basbaum, 1999). Furthermore, we have demonstrated anatomically that Off-cells receive a dense noradrenergic input (Meng et al, 1997). The current finding that blockade of ␣ 1receptors by prazosin considerably attenuates PAG DAMGOinduced analgesia indicates that activation of noradrenergic synaptic inputs acting on ␣ 1 -receptors directly excites NRM primary cells (Off-cells) and is required for the antinociceptive effect of PAG opioids (Fig.…”
Section: Roles Of Nr⌴ ␣ 1 -And ␣ 2 -Adrenoceptors In Opioid Modulatiosupporting
confidence: 81%
See 2 more Smart Citations
“…Our previous studies have shown that excitation of RVM Offcells, or primary cells identified in vitro, mediates the analgesia induced by PAG DAMGO, consistent with their proposed inhibitory action on spinal pain transmission (Pan et al, 1997;Fields and Basbaum, 1999). Furthermore, we have demonstrated anatomically that Off-cells receive a dense noradrenergic input (Meng et al, 1997). The current finding that blockade of ␣ 1receptors by prazosin considerably attenuates PAG DAMGOinduced analgesia indicates that activation of noradrenergic synaptic inputs acting on ␣ 1 -receptors directly excites NRM primary cells (Off-cells) and is required for the antinociceptive effect of PAG opioids (Fig.…”
Section: Roles Of Nr⌴ ␣ 1 -And ␣ 2 -Adrenoceptors In Opioid Modulatiosupporting
confidence: 81%
“…Increasing evidence suggests that activation of these -expressing medullary cells accounts at least partially for the increased pain sensitivity, or hyperalgesia, during opioid withdrawal and in other chronic pain states (Bederson et al, 1990;Kaplan and Fields, 1991;Pan et al, 2000;Porreca et al, 2001Porreca et al, , 2002. These cells also receive a dense NA input (Meng et al, 1997). Our observation that ␣ 1 -receptor blockade attenuates opioid withdrawal-induced hyperalgesia indicates that noradrenergic inputs excite NRM secondary cells through ␣ 1 -receptors and that this excitation of secondary cells is required for the hyperalgesia during opioid withdrawal (Fig.…”
Section: Roles Of Nr⌴ ␣ 1 -And ␣ 2 -Adrenoceptors In Opioid Modulatiomentioning
confidence: 61%
See 1 more Smart Citation
“…This implies that pronociceptive effects would originate from neurons localized more dorsally in the LC. By contrast, both inhibitory and facilitatory effects of the RVM, another structure responsible for the bidirectional modulation of pain, are thought to be mediated by interspersed bulbospinal projections from pain‐inhibitory (OFF‐cell) and excitatory (ON‐cell) projection neurons that both receive direct noradrenergic innervation (Meng et al, ; Porreca et al, ; Suzuki et al, ; Heinricher, et al, ).…”
Section: Bidirectional Modulation Of Pain By the Lcmentioning
confidence: 99%
“…Norepinephrine has also been shown to play a role in nociceptive modulation at the level of the RVM. Both "on-" and "off-cells" have been demonstrated to be targets of descending noradrenergic projection neurons (Meng et al, 1997). Moreover, both facilitatory and inhibitory effects on nociception have been demonstrated for noradrenergic compounds within the RVM, and appear to involve different receptor subtypes.…”
Section: Modulation Of Nociception Within the Rostral Ventromedial Mementioning
confidence: 99%